Measuring academic productivity in higher education: A bibliometric analysis of output and scientific impact - Ruhita, Ruhita (Universitas Jambi, Indonesia, 2025)
This research presents a bibliometric analysis of academic productivity research in higher education from 2015 to 2025, based on 241 Scopus-indexed journal articles. Using VOSviewer and Biblioshiny, the analysis identifies influential papers, institutions, and countries, revealing that the United States and China are the most productive contributors, with strong international collaborations (23.65% co-authorship). The publication trend shows a steady increase, with no decline during the COVID-19 period, indicating the persistent relevance of this research area. Keyword mapping highlights five key research clusters: scientific productivity, research impact, efficiency measurement, human capital, and institutional factors. Despite advancements, gaps remain in the role of AI, digital transformation, and faculty well-being in academic productivity. Future research should focus on data-driven efficiency models and sustainability in higher education. This investigation offers helpful insights for policymakers and institutions aiming to